PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI BERBASIS CLOUD COMPUTING TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KOTA MEDAN - Syahputra, Heri Enjang; Simanjuntak, Owen De Pinto; Purba, Rosana; Zega, Susilawati (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to determine the influence of cloud computing-based accounting information systems on the performance of Micro, Small and Medium Enterprises (MSMEs) in Medan city. The number of samples is 93 MSMEs. Data were collected using online questionnaires distributed to respondents. The research method used is descriptive statistics with quantitative approach. The results of this study conducted found that the Sig. value of 0.000 < 0.05 and a regression coefficient value of 0.377, which indicates that the cloud computing-based accounting information system has influence on the MSMEs performance. The value of t count > t table of 5.747 > 2.990, which means that there is an impact of cloud computing-based accounting information systems on MSMEs performance. Pearson Correlation value 0.516 (r count) > 0.207 (r table) which means there is a positive correlation between cloud computing-based accounting information system variables and MSMEs performance. R Square value of 0.266 indicates the impact of cloud computing-based accounting information systems on MSMEs performance is 26.6%, while 73.4% is affected by other factors outside of thisstudy.